UG or not UG: Where is Recursion? - Atkinson, Martin; Al-‐Mutairi, Fahad (IBERIA: An International Journal of Theoretical Linguistics, 2014)
The operation Merge, applying to two syntactic objects to produce a third and instantiating the property of recursion, has been a fundamental and largely uncontroversial feature in the development of the Minimalist Programme. In early formulations, such as Chomsky (1995a, b), Merge is cited as a feature of the human language faculty that illustrates virtual conceptual necessity, and it is an examination of this characterisation that stimulates the concerns addressed here, where we argue that neither of the familiar routes (satisfaction of interface conditions or computational economy) provides a justification for the conceptually necessary status of Merge. A third route, via considerations of ‘languages as such,’ a notion that includes human and artificial languages, may provide the required justification, but, as Chomsky (1980) urges, the study of ‘languages as such’ is unlikely to yield empirically interesting results. Specifically, this route to justification will not locate Merge in UG if the content of UG is an empirical matter. This conclusion is damaging to the view (Hauser et al., 2002) that the emergence of recursion (and Merge) is the single development crucial to the evolution of language, an empirical proposal, albeit in a different discourse, that firmly places Merge in UG.